Uncertainty-Weighted Time Averaging of Mercury Vapour Concentrations in Ambient Air: Application to Measurements in the United Kingdom - Richard J. C. Brown; Dharsheni Muhunthan (The Scientific World Journal)
Uncertainty-weighted time averaging of total gaseous mercury concentrations in ambient air, with associated robust uncertainties, has been performed for concentrations measured by the U.K. Heavy Metals Monitoring Network between 2007 and 2009. The results have been compared with averages produced using standard time-averaging methods with a view to investigating the properties of the new method and whether it represents an improvement over current practice.